Penerapan Metode Monte Carlo Dalam Memprediksi Jumlah Penerima Al-Quran Tulis Di Sumatera Utara - Rambe, Siti Rahmi; Miftah Pratiwi; Meysin Andira; Sajaratud Dur (Jurnal Pengabdian Masyarakat, 2022)
Al-Qur’an is the holy book of Muslims that needs to be learned and practiced by every musli. Reading and writing the koran is something that must be learned by all muslims,especially the younger generation,by making children and the environment able to read the koran when children are still in elementary school,making children able to memorize a lot short letters and can recite prayers.writing the Qur’an by hand one page for 15 minute every day will improve writing skills.the form of monte carlo where the solution simulation is also from a problem that arises is given based on randomness and calculates from a probability value with a good objective value basedon the distribution data used.